2022
DOI: 10.20945/2359-3997000000428
|View full text |Cite
|
Sign up to set email alerts
|

Cushing disease due to a somatic USP8 mutation in a patient with evolving pituitary hormone deficiencies due to a germline GH1 splicing variant

Abstract: We present the unique case of an adult Brazilian woman with severe short stature due to growth hormone deficiency with a heterozygous G to T substitution in the donor splice site of intron 3 of the growth hormone 1 (GH1) gene (c.291+1G>T). In this autosomal dominant form of growth hormone deficiency (type II), exon 3 skipping results in expression of the 17.5 kDa isoform of growth hormone, which has a dominant negative effect over the bioactive isoform, is retained in the endoplasmic reticulum, disrupts the Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…In a study focused on pediatric patients with ACTH PitNETs, USP8 mutations were found in 31% of cases. However, USP8 mutation carriers generally have small tumor size, which is no more than 5 mm (41). In this case, the preoperative dynamic contrast-enhanced MRI of the patient revealed a tumor size of 51mm, with upward extension into the suprasellar cistern, depression of the sellar floor bone, significant compression and elevation of the optic chiasm, and bilateral CS invasion, classified as knosp grade 4, displaying a diffuse and invasive growth pattern.…”
Section: Discussionmentioning
confidence: 80%
“…In a study focused on pediatric patients with ACTH PitNETs, USP8 mutations were found in 31% of cases. However, USP8 mutation carriers generally have small tumor size, which is no more than 5 mm (41). In this case, the preoperative dynamic contrast-enhanced MRI of the patient revealed a tumor size of 51mm, with upward extension into the suprasellar cistern, depression of the sellar floor bone, significant compression and elevation of the optic chiasm, and bilateral CS invasion, classified as knosp grade 4, displaying a diffuse and invasive growth pattern.…”
Section: Discussionmentioning
confidence: 80%
“…78 A somatic USP8 mutation was found in an adult patient with Cushing's disease, who also suffered from growth hormone deficiency due to GH1 mutation. 79 USP8 mutations were also detected in 13/45 paediatric patients with Cushing's disease, but not in a single centre study of 18 paediatric patients. 70,80 All USP8 mutations reported are somatic, but a case of heterozygous germline USP8 hotspot mutation in a paediatric patient with Cushing's disease has recently been reported.…”
Section: Ubiquitin Specific Protease 8 (Usp8)mentioning
confidence: 82%
“…A somatic USP8 mutation was found in the corticotroph tumour of a patient that presented with both adrenal Cushing's syndrome and central Cushing's disease and additionally carried somatic mutation in NR3C1 in the corticotroph tumour and CTNNB1 in the adrenal tumour 78 . A somatic USP8 mutation was found in an adult patient with Cushing's disease, who also suffered from growth hormone deficiency due to GH1 mutation 79 …”
Section: Sporadicmentioning
confidence: 96%